2021
DOI: 10.1007/s10533-021-00818-3
|View full text |Cite
|
Sign up to set email alerts
|

Elevated salinity and water table drawdown significantly affect greenhouse gas emissions in soils from contrasting land-use practices in the prairie pothole region

Abstract: Elevated salinity and water table drawdown significantly affect greenhouse gas emissions in soils from contrasting land-use practices in the prairie pothole region

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Another possible explanation is depletion of soil organic carbon and total N at the experimental site, because of the local practice of not returning crop residues to the soil. In addition, the soil at the study site is moderately saline and studies on paddy fields have found that soil salinity affects CH 4 emissions through suppressing the activities of soil microbes, including methanogens [34,35]. However, the soil salinity conditions were improved prior the present study and the soil salinity effect was probably limited.…”
Section: Accumulated Ghg Fluxesmentioning
confidence: 72%
See 1 more Smart Citation
“…Another possible explanation is depletion of soil organic carbon and total N at the experimental site, because of the local practice of not returning crop residues to the soil. In addition, the soil at the study site is moderately saline and studies on paddy fields have found that soil salinity affects CH 4 emissions through suppressing the activities of soil microbes, including methanogens [34,35]. However, the soil salinity conditions were improved prior the present study and the soil salinity effect was probably limited.…”
Section: Accumulated Ghg Fluxesmentioning
confidence: 72%
“…Methanogenic bacteria are very sensitive to variations in soil pH, with the highest CH 4 production rates at neutral pH and with small changes in soil pH sharply lowering CH 4 production [33]. High soil salt content decreases CH 4 emissions, through suppressing the activities of soil microbes, including methanogens [34,35]. The reported effects of soil salinity on N 2 O emission are inconsistent (increase, decrease or no response) [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, saline water irrigation (SWI) brings salt into the soil. Some studies found salt could affect microbial processes of soil C and N cycles ( Poffenbarger et al, 2011 ; Yu et al, 2019 ; Shahariar et al, 2021 ). Our previous research has also found that SWI alters the content of soil environmental factors involved in C and N cycles, such as soil organic matter, inorganic N, and greenhouse gasses ( Zhou et al, 2023 , 2024 ).…”
Section: Introductionmentioning
confidence: 99%